2010
DOI: 10.3109/07434618.2010.522200
|View full text |Cite
|
Sign up to set email alerts
|

Differences Among Sighted Individuals and Individuals with Visual Impairments in Word Intelligibility Presented via Synthetic and Natural Speech

Abstract: This study investigated word intelligibility among sighted individuals and individuals with visual impairments for both natural and synthetic speech. Both groups of participants performed significantly better when identifying words presented via natural speech. The results also demonstrated that individuals with visual impairments were more successful than their sighted peers in understanding words presented via synthetic speech, with experience being the most critical factor in identifying words for the parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…They can perform their daily routine tasks easily i.e., communicating with their friends, easily accessing information and enhancing their learning skills. Earlier research showed that the focus was shifted in visually impaired people from vision to hearing in eye free environment because their hearing power is more than normal people [12][13]. Due to the inception of advanced technology in recent years, many human problems cured and new innovative applications have been proposed by researchers to handle different problems effectively (accessing mathematics material is one of them).…”
Section: Related Workmentioning
confidence: 99%
“…They can perform their daily routine tasks easily i.e., communicating with their friends, easily accessing information and enhancing their learning skills. Earlier research showed that the focus was shifted in visually impaired people from vision to hearing in eye free environment because their hearing power is more than normal people [12][13]. Due to the inception of advanced technology in recent years, many human problems cured and new innovative applications have been proposed by researchers to handle different problems effectively (accessing mathematics material is one of them).…”
Section: Related Workmentioning
confidence: 99%